Users satisfaction towards maintenance service quality on university building / Nur Syazwani Mohamad Shahar - Mohamad Shahar, Nur Syazwani (Faculty Architecture, Planninng and Surveying, 2015)
University building is an important place to get the proper maintenance management because the good environments for the occupants can help to boost the positive energy from them to more motivate while learning or working at the university. In Malaysia, building maintenance management for building university are lacking in giving the good maintenance service quality for the occupant cause the occupant also did not take the maintenance as a big issue to be considered. This study involves to improving the service quality of building maintenance management system for University building. The goal is to identify the current practices and procedures of building maintenance management for University. This had been done by using interview session method to gain the information about the University’s current practices and procedures at the selected case study. The case study was at three (3) local University in Malaysia such as UiTM (Universiti Teknologi Mara), UPM (Universiti Putra Malaysia) and UKM (Universiti Kebangsaan Malaysia) by conducting the interview with the maintenance management officers of each University. While conducting the interview session, researcher also gets to know the problem faced by building maintenance management for managing the University building. Other finding method used, was questionnaire survey to investigate the satisfaction of the students and staffs towards maintenance service quality on University building.